Ovarian cancer and the immune system - Thaïs Baert; Ignace Vergote; An Coosemans (Elsevier, 2017)
Short communication in response to the review of Turner et al. entitled "Ovarian cancer and the immune system - the role of targeted therapies" published in Gynecological Oncology. We believe systemic immune parameters might be a good alternative to tumor biopsy to gain insight in the immunological background of ovarian cancer.